The Role of Musharakah in the Economic Development of Tehsil Dargai, District Malakand, Khyber Pakhtunkhwa, Pakistan - Suhail Ahmad; Ejaz Aslam; Prof. Dr. S. Ghiasul Haq; Prof. Dr. Mohd Ma'Sum Billah (Islamic Banking and Finance Review, 2019)
Islamic finance industry has been growing for the last twenty years, both in Muslim and non-Muslim countries around the world. There are different modes of Islamic finance which provide job opportunities across the globe. In Pakistan, the contemporaneous growth of Islamic banking and finance is not different from other countries. Islamic banking and finance does not only provide employment for individuals, indeed it also offers various products and services to customers across the country. Musharakah is a form of business in Islamic finance that is being adopted rapidly by most of the customers in Islamic banking and finance institutions. Therefore, the purpose of this study is to examine the role of Islamic finance, mainly how Musharakah is playing its due role in creating employment and maintaining sustainable development projects which in turn are causes of the development of the economy, particularly of Tehsil Dargai. For this purpose, this study collected data through a questionnaire that was randomly distributed among 100 respondents in Tehsil Dargai, District Malakand, Khyber Pakhtunkhwa (KP), Pakistan and the response rate was 60%. We found that Islamic finance is rapidly growing in Dargai; indeed, people are practicing different modes of Islamic finance and Musharakah is the most popular form of Islamic finance in this area. This study utilizes limited data because it was only conducted in Dargai.